Stakeholders matter a new paradigm for strategy in society - Sachs, Sybille; Ruhli, Edwin; ProQuest (Firm) (Cambridge ; New York : Cambridge University Press, 2011)
"The dominant shareholder-value model has led to mismanagement, market failure and a boost to regulation, as spectacularly demonstrated by the events surrounding the recent financial crisis. Stakeholders Matter challenges the basic assumptions of this model, in particular traditional economic views on the theory of the firm and dominant theories of strategic management, and develops a new understanding of value creation away from pure self-interest toward mutuality. This new 'stakeholder paradigm' is based on a network view, whereby mutuality enhances benefits and reduces risks for the firm and its stakeholders. The understanding of mutual value creation is operationalized according to the license to operate, to innovate and to compete. The book develops a vision for a strategy in society in which, rather than the invisible hand of the market, it the visible hands of the firm and the stakeholders that lead to an overall increase in the welfare of society"--
Machine generated contents note: List of figures; List of tables; Foreword Edward Freeman; 1. Challenges for a new paradigm in strategic management; Part I. Development of the Basic Assumptions of a New Stakeholder Paradigm: 2. The economic paradigm and its basic assumptions; 3. Contribution of stakeholder theory to our understanding of the stakeholder paradigm; 4. The stakeholder paradigm; Part II. Our Understanding of the Stakeholder Paradigm and its Operationalization: 5. Our understanding of the stakeholder paradigm operationalized in the three licenses; 6. License to operate; 7. License to innovate; 8. License to compete; 9. Challenges resulting from a paradigm shift; Appendix; Glossary; Notes; Bibliography.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Strategic planning; Customer relations; Electronic books